The Prevalence of Restless Legs Syndrome in Patients with Migraine: A Systematic Review and Meta-Analysis - Hooman Ghasemi; Behnam Khaledi-Paveh; Alireza Abdi; Rostam Jalali; Nader Salari; Aliakbar Vaisi-Raygani; Masoud Mohammadi (Pain Research and Management)
Background. Migraine is a severe and debilitating neurologic disorder and is claimed to be the sixth disabling illness in the world. This study aimed to determine the overall prevalence of restless legs syndrome (RLS) in patients with migraine through a systematic review and meta-analysis. Methods. To identify and select related studies, the Scopus, ScienceDirect, Embase, SID, IranDoc, Web of Science, Knowledge Network System Medline (PubMed), and Google Scholar databases were searched. All related cross-sectional studies, published in English or Persian language between January 2000 and December 2019 and using the keywords such as migraine, restless leg syndrome, sleep disorder, RLS, and migraine disorder, were collected. The heterogeneity of the studies was assessed using the I2 index, and the data analysis was performed using the Comprehensive Meta-Analysis software. Results. Analysis was conducted on the reported results of the final 12 articles with the total sample size of 15196. The overall prevalence of RLS in patients with migraine was 16.3% (95% CI: 12.6–20.8%). The prevalence of RLS migraine patients decreased with increasing the sample size, and the prevalence of RLS migraine patients increased with increasing the research year, which was statistically significant (P<0.05). Conclusion. This study highlights that RLS is high in patients with migraine, and therefore, the clinicians should be aware of its incidence and take preventive measures.